The mesoscale organization of syntaxin 1A and SNAP25 is determined by SNARE–SNARE interactions - Jasmin Mertins (eLife Sciences Publications Ltd, 2021)
SNARE proteins have been described as the effectors of fusion events in the secretory pathway more than two decades ago. The strong interactions between SNARE domains are clearly important in membrane fusion, but it is unclear whether they are involved in any other cellular processes. Here, we analyzed two classical SNARE proteins, syntaxin 1A and SNAP25. Although they are supposed to be engaged in tight complexes, we surprisingly find them largely segregated in the plasma membrane. Syntaxin 1A only occupies a small fraction of the plasma membrane area. Yet, we find it is able to redistribute the far more abundant SNAP25 on the mesoscale by gathering crowds of SNAP25 molecules onto syntaxin clusters in a SNARE-domain-dependent manner. Our data suggest that SNARE domain interactions are not only involved in driving membrane fusion on the nanoscale, but also play an important role in controlling the general organization of proteins on the mesoscale. Further, we propose these mechanisms preserve active syntaxin 1A–SNAP25 complexes at the plasma membrane.